A cationic alternating copolymer composed of ornithine and glycine with an ordered sequence for enhanced bacterial activity. Issue 5 (8th February 2021) - Liu, Fuqiang; Ma, Nan; Liu, Jun; Zhu, Qiongqiong; Yue, Ting; Ma, Junhui; Wang, Yuan; Qu, Wei; Chu, Paul K.; Tang, Yan; Zhang, Wei
Abstract: The chains and segments of unordered cationic polypeptides are complex and may produce unexpected biological activities. Herein, the Ugi's 4CC reaction is adopted to synthesize a cationic alternating copolymer comprising ornithine and glycine (poly(Orn‐alter‐Gly)) with an ordered sequence for enhanced bacterial resistance. In this technique, potassium isocyanate, 4‐(N‐carbobenzyloxyamino)‐1‐butyraldehyde and 1‐(4‐Methoxyphenyl)ethylamine react to produce MPE‐substituted poly(Orn‐alter‐Gly) in one step without using a catalyst and then poly(Orn‐alter‐Gly) is obtained by removing the N‐(1‐p‐methoxyphenethyl) (MPE) group. 1 H NMR, Fourier transform infrared spectroscopy, and automatic amino acid analysis confirm that ornithine and glycine are linked alternately in the poly(Orn‐alter‐Gly) chains. Both MPE‐substituted poly(Orn‐alter‐Gly) and poly(Orn‐alter‐Gly) have excellent antibacterial activity against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa as well as excellent biocompatibility. The synthesis strategy and materials provide new information on how to obtain ordered sequence cationic polypeptides. Abstract : A cationic alternating copolymer composed of ornithine and glycine with an ordered sequence.